Fundamentals of athletic training - Cartwright, Lorind 1956- (Human Kinetics, 2019)
Fundamentals of Athletic Training, Fourth Edition, provides a clear understanding of the functions, skills, and activities that are involved in the work of certified athletic trainers. This book helps students evaluate the possibility of a career as a sports medicine professional.